Form-Focused Instruction in the Heritage Language Classroom: Toward Research-Informed Heritage Language Pedagogy - Kisselev, Olesya; Dubinina, Irina; Polinsky, Maria (Frontiers in Education, 2020)
Heritage language speakers have been recognized as a special group of language learners, whose knowledge of and experiences with the language, as well as their motivations for (re)learning their home language, differ drastically from that of an average learner of a second language. Current heritage language pedagogical approaches mainly focus on the development of communicative (or functional) abilities of the heritage learners; however, heritage speakers continue to struggle with structural accuracy and complexity of their speech and, thus, often fail to develop higher levels of proficiency in their heritage language. In this paper, we propose that focus-on-form needs to be an integral part of teaching heritage learners from the start of instruction. We base our argument on the results of extensive linguistic research on heritage Russian and on insights from the currently available pedagogically oriented classroom and laboratory-based research on heritage learners. We formulate and discuss instructional methods that help educators develop heritage learners’ attention to grammatical form and ability to recognize form-meaning mappings; foster conceptual understanding of grammar, and increase their metalinguistic awareness. Given consistent parallels across different heritage languages, the methodologies developed for Russian learners readily apply in other heritage language classrooms as well.